1 Congenitally corrected transposition of the great arteries: indications for CRT?. (28th April 2017) - Bell, A; Clift, P; Thorne, S; Bowater, S; Marshall, H; Bono, J de; Hudsmith, L
Abstract : Background: Congenitally corrected transposition of the great arteries (ccTGA) is a rare congenital heart defect. Late complications include systemic ventricular failure, systemic AV valve regurgitation, AV conduction problems and arrhythmias. Heart Rhythm Society (HRS) published expert consensus statement regarding arrhythmia management in congenital heart disease, including Cardiac Resynchronisation Therapy (CRT) indications for adult congenital heart disease (ACHD) patients. These include EF <35% with RV dilatation, NYHA II-IV, RBBB, QRS duration >150 ms in non-paced and if paced NYHA I-IV and >40% V-pacing Method: Review of notes for Class IIa indications for CRT device in ccTGA. Results: 55 patients were identified; mean age was 43.6±16 years. 36 patients (65%) had impaired systemic ventricular dysfunction on echo, mild (n=10), moderate (n=20) or severe (n=6). 31 (56%) of all patients had systemic AV valve regurgitation: mild (n=12), moderate (n=15) or severe (n=4). 12 (22%) patients have undergone systemic AV valve replacement surgery. Rhythm was sinus (60%, n=33) or paced (n=15) on ECG. 5 (9%) were in atrial fibrillation, 4 (7%) 1st degree heart block. 18 (30%) had a simple pacemaker and 2 a CRT device. 4 (7%) fulfilled Class IIa indications for a CRT device, of which 2 had a simple pacemaker Conclusion: Only a small proportion of ccTGA patients fulfil Class IIa indications for CRT. However, complex anatomy and previous surgery may render implantation difficult. Each case needs to be assessed individually with combined electrophysiology and ACHD input with care translating guidelines into clinical practice.